2007
DOI: 10.1534/genetics.107.071472
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Chaperone Hsp90 Is Required for mRNA Localization in Drosophila melanogaster Embryos

Abstract: Localization of maternal nanos mRNA to the posterior pole is essential for development of both the abdominal segments and primordial germ cells in the Drosophila embryo. Unlike maternal mRNAs such as bicoid and oskar that are localized by directed transport along microtubules, nanos is thought to be trapped as it swirls past the posterior pole during cytoplasmic streaming. Anchoring of nanos depends on integrity of the actin cytoskeleton and the pole plasm; other factors involved specifically in its localizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 69 publications
1
24
0
Order By: Relevance
“…Although this graph was corrected for non-linearity of the staining method, it is not consistent with our analysis using modern experimental and analytical tools (see below). In addition, in some cases a bcd mRNA gradient can indeed be observed but was missed or ignored (T. Berleth, PhD thesis, University of Tübingen, 1988) (Berleth et al, 1988;St Johnston et al, 1989;Schnorrer et al, 2002;Song et al, 2007).…”
Section: Revisiting the Bcd Mrna Gradientmentioning
confidence: 99%
“…Although this graph was corrected for non-linearity of the staining method, it is not consistent with our analysis using modern experimental and analytical tools (see below). In addition, in some cases a bcd mRNA gradient can indeed be observed but was missed or ignored (T. Berleth, PhD thesis, University of Tübingen, 1988) (Berleth et al, 1988;St Johnston et al, 1989;Schnorrer et al, 2002;Song et al, 2007).…”
Section: Revisiting the Bcd Mrna Gradientmentioning
confidence: 99%
“…HSP90 is also required for normal spermatogenesis, oogenesis, and embryogenesis in Drosophila spp. (Yue et al 1999;Song et al 2007;Pisa et al 2009). Recent studies have confirmed that HSP90 has been thought to have evolutionarily conserved functions that contribute to oogenesis and compound eye development in the red flour beetle Tribolium castaneum (Xu et al 2010;Knorr and Vilcinskas 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although mutations that cause defects in nos localization have been identified in numerous genetic screens, the effects of these mutations on nos are most likely to be indirect, as they disrupt localization or assembly of germ plasm. A recent genetic screen for nos localization factors identified the chaperone Hsp90 (also known as Hsp83 -FlyBase) as being important for nos localization, though its role also appears to be indirect (Song et al, 2007). Given the redundancy within the nos localization signal and, consequently, the potential for functional redundancy among proteins that interact with different nos localization elements, genetic approaches may fail to identify direct-acting localization factors.…”
Section: Introductionmentioning
confidence: 99%